A METHOD FOR ACTIVITY CALCULATIONS IN SALINE AND MIXED SOLVENT SOLUTIONS AT ELEVATED TEMPERATURE AND PRESSURE: A FRAMEWORK FOR GEOLOGICAL PHASE EQUILIBRIA CALCULATIONS - Evans K.; Powell R. (My University, 2006)
Quantitative thermodynamic calculations that involve aqueous fluids have proved difficult because of the complexity of the interactions that occur within the fluids. Existing thermodynamic models are difficult to apply to mixed solvent or highly saline solutions at P > 0.3 GPa and T > 300 °C. This work constructs a method for activity-composition calculations in saline, mixed solvent, supercritical aqueous solutions. Mixing is formulated on a mole-fraction scale in terms of a set of independent end-members that describe composition and speciation within the solution. The ideal mixing term takes speciation into account and avoids problems with the common ion effect. Non-ideal interactions are represented by an activity coefficient term that combines a limited form of Debye-Hückel and a van Laar formulation. This approach, referred to as the DH-ASF model, is thermodynamically valid over a wide range of P, T and fluid composition. The value of the model lies in its broad applicability, and small number of calibration parameters. Experimental data from the literature for the systems NaCl-H2O, KCl-H2O, H2O-SiO2-CO2, H2O-NaCl-CO2, H2O-NaCl-SiO2 and for H2O-albite melts have been used to calibrate the DH-ASF model. Calculations were performed using Thermocalc, computer software that calculates equilibria for mineral-based chemical systems.1The current version of Thermocalc and the internally consistent dataset can be obtained from http://www.earthsci.unimelb.edu.au/tpg/thermocalc/.1 The model represents the data to within experimental error in most cases. Conditions modelled include pressures between 0.2 and 1.4 GPa, temperatures between 500 and 900 °C, and xH2 O from 0.1 to 1. Calibrated parameters are consistent with expectations based on the conceptual model for the fluid, and are relatively insensitive to changes in pressure and temperature for most examples. The DH-ASF model is thermodynamically valid for a range of P-T conditions that includes pressures from 0.1 to 2 GPa and temperatures from 200 to 1000 °C. A lack of experimental data restricts calibration of the model for many end-members. However, it may be possible to neglect parameters associated with end-members present in small amount. In this case, or with new experimental data for calibrations, the DH-ASF model allows previously inaccessible geological systems and processes to be modelled. © 2006 Elsevier Inc. All rights reserved.